POTENSI NILAI KARAKTER DOKTER CIPTO MANGUNKUSUMO DALAM PEMBELAJARAN SEJARAH GUNA MENUMBUHKAN WAWASAN KEBANGSAAN - Pramesti, Shendy Dyah; Yuliati, Yuliati (Universitas Negeri Malang, 2024)
Abstract: Through the Kurikulum Merdeka, character education integrated in the history learning is one of the solutions in dealing with challenges in education. The fading awareness of cultural values and love for the homeland indicates a lack of national characteramong students. In this context, character education plays a crucial role in fostering the national insight within students. One of the ways to develop national insight among students is through the exemplary role of prominent figures. Dr. Cipto Mangunkusumo emerges as a notable figure whose qualities can serve as a model for students in cultivating national character and insight. This research employs a qualitative approach with a literature study method. The aim of this research is to explore the potential character values of Dr. Cipto Mangunkusumo in nurturing national insight through history education. The result of this research is the discovery of the potential character values of Dr. Cipto Mangunkusumo which can be adopted and integrated into the values of national insight through six fundamental dimensions, namely 1) respect for the value and dignity of humans as creatures created by God Almighty; 2) determination for free, independent and united national life; 3) love for the nation and motherland; 4) democracy and people's sovereignty; 5) social solidarity; 6) a just and prosperous society. The aspects of Dr. Cipto's character values also can be implemented into the Independent Curriculum Pancasila Student Profile guidelines, namely 1) having faith and being devoted to God Almighty; 2) work together; and 3) critical reasoning. Abstrak: Melalui Kurikulum Merdeka, pembelajaran sejarah yang terintegrasi pendidikan karakter merupakan sebuah solusi dalam menangani tantangan dunia pendidikan. Pudarnya kesadaran terhadap sosok dan peran para pahlawan nasional menandakan kurangnya karakter kebangsaan dalam diri siswa. Dalam hal ini, pendidikan karakter memiliki peran penting untuk menumbuhkan wawasan kebangsaan yang ada pada diri siswa. Salah satu cara yang dapat digunakan untuk mengembangkan wawasan kebangsaan dalam diri siswa adalah melalui teladan parah tokoh. Salah satu tokoh penting yang dapat dijadikan contoh untuk menumbukan karakter dan wawasan kebangsaan adalah Dokter Cipto Mangunkusumo. Penelitian ini menggunakan jenis pendekatan kualitatif dengan metode studi literatur. Penelitian ini bertujuan untuk mengeksplorasi potensi nilai karakter Dokter Cipto Mangunkusumo dalam dalam menumbuhkan wawasan kebangsaan melalui pembelajaran sejarah. Hasil dari penelitian ini adalah ditemukannya potensi nilai-nilai karakter Dokter Cipto Mangunkusumo yang dapat diadopsi dan diintegrasikan ke dalam nilai-nilai wawasan kebangsaan melalui enam dimensi fundamental, yaitu 1) penghargaan terhadap harkat dan martabat manusia sebagai makhluk ciptaan Tuhan YME; 2) tekad bersama untuk kehidupan berbangsa yang bebas, merdeka, dan bersatu; 3) cinta bangsa dan tanah air;4) demokrasi dan berkedaulatan rakyat; 5) kesetiakawanan sosial; 6) masyarakat yang adil dan makmur. Aspek nilai karakter Dokter Cipto juga dapat diimplementasikan ke dalam pedoman Profil Pelajar Pancasila Kurikulum Merdeka, yaitu 1) beriman dan bertakwa kepada Tuhan YME; 2) bergotong royong; dan 3) bernalar kritis.